How Tuzla welcomed the creation of the Kingdom of Serbs, Croats and Slovenes - Jahić, Adnan (Historical Thought, 2025)
This article tells about the events in Tuzla in November and December 1918, before and after the formation of the Kingdom of Serbs, Croats and Slovenes. The author describes how certain groups and communities as well as public figures and ordinary people reacted to the new situation after the disappearance of the Austro-Hungarian rule and the establishment of the Yugoslav state, in which way the sensitive communication between different levels of government in the area of Tuzla and its surroundings took place in the days of the interregnum and to what extent the ghosts of the recent past influenced the attitudes and behaviour of people in a time of great change and new opportunities.